On some trigonometric and hyperbolic functions evaluated on circulant matrices - Bueno, Aldous Cesar F (Scientia magna, 2013)
In this paper, we investigate the outcome when the trigonometric functions sin x, cos x, [e.sup.x] and the hyperbolic functions sinh x and cosh x are evaluated on circulant matrices. Keywords circulant matrix, trigonometric functions, hyperbolic functions. 2000 Mathematics Subject Classification: 54Dl5,54DlO